Dix ans de nouvelles : une anthologie québécoise - Pellerin, Gilles (L'Instant Même)
Contiene cuentos de: Jean-Paul Beaumier, Sylvaine Tremblay, Danielle Dussault, Claude-Emmanuelle Yance, Hugues Corriveau, Sylvie Massicotte, Guy Cloutier, Suzanne Lantagne, Gilles Pellerin, Normand de Bellefeuille, Christiane Lahaie, Diane-Monique Daviau, Olga Boutenko, Maurice Henrie, Jean Pierre Girard, Bertrand Bergeron, Claudine Potvin, Michel Dufour, Jean Pelchat, Louise Cotnoir, Wilhelm Scwartz, Louis Jolicoeur, Pierre Yergeau, Anne Legault, Roland Bourneuf y Pierre Ouellet.